Microbiological and Antibiotic Profile of Tracheal Aspirate in Mechanically Ventilated Patients in a Tertiary Hospital - Basnet, Rajan; Bhandari, Dixya; Shrestha , Rajani (Nepal Journal of Medical Sciences, 2025)
Introduction: Ventilator-associated pneumonia (VAP) is a prevalent hospital-acquired infection in mechanically ventilated patients, leading to increased morbidity, mortality, and antimicrobial resistance. Early identification and understanding of microbiological patterns and antibiotic susceptibility are crucial to optimizing treatment strategies. Methods:A cross-sectional study was conducted in the ICU of Manipal College of Medical Sciences, Pokhara, from March 5, 2024, to March 6, 2025. Patients on mechanical ventilation for >72 hours exhibiting signs of infection were included. Endotracheal aspirates were obtained and cultured. Pathogens were identified, and antibiotic susceptibility testing was performed. Data were analyzed using SPSS to determine the prevalence, microbiological profile, and antibiotic resistance patterns. Results: Of 107 patients, 75 (70.1%) had culture-positive tracheal aspirates. The predominant organisms were Gram-negative bacteria (62.5%), notably Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa. A. baumannii showed complete resistance to first-line antibiotics and 92.6% resistance to carbapenems, while all isolates remained sensitive to polymyxin B, colistimethate, and tigecycline. K. pneumoniae demonstrated 60–93.3% resistance to cephalosporins and aminoglycosides. P. aeruginosa was moderately resistant to beta-lactams but susceptible to carbapenems and aminoglycosides. Fungal isolates (Candida spp.) accounted for 4.7%, and Staphylococcus aureus for 2.8%. Conclusions:This study underscores a high burden of VAP in ICU patients, predominantly caused by multidrug-resistant Gram-negative pathogens. The alarming resistance to first-line antibiotics necessitates robust infection control measures and prudent antibiotic use. Targeted empirical therapy guided by local microbiological trends is vital to improving patient outcomes in mechanically ventilated populations.